2011
DOI: 10.1002/jcu.20853
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic plantar fibroma with a unique sonographic appearance

Abstract: We present a case of a solitary plantar fibroma with unique sonographic features with MRI and pathologic correlation. A 25-year-old woman presented with a left foot mass that interfered with her gait. Sonography demonstrated a well-circumscribed, 32 mm × 27 mm × 14 mm subcutaneous mass with heterogeneous echogenicity. Unique sonographic characteristics included posterior acoustic enhancement, cystic components, and mild intratumoral hypervascularity. MRI confirmed the sonographic findings. Surgical excision wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Intrinsic vascularity was seen in 53% of patients, which was in contrast to the most recent large cohort which showed vascularity in only 8% of lesions . Vascularity was not graded in the study by Griffith et al, but our cohort showed 20% of lesions with moderate and marked vascularity, compatible with a prior report that lesions may have substantial increased intrinsic vascularity . The presence of vascularity in our series may be reflective of newer US technology being more sensitive.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Intrinsic vascularity was seen in 53% of patients, which was in contrast to the most recent large cohort which showed vascularity in only 8% of lesions . Vascularity was not graded in the study by Griffith et al, but our cohort showed 20% of lesions with moderate and marked vascularity, compatible with a prior report that lesions may have substantial increased intrinsic vascularity . The presence of vascularity in our series may be reflective of newer US technology being more sensitive.…”
Section: Discussionsupporting
confidence: 75%
“…8 Vascularity was not graded in the study by Griffith et al, 8 but our cohort showed 20% of lesions with moderate and marked vascularity, compatible with a prior report that lesions may have substantial increased intrinsic vascularity. 20 The presence of vascularity in our series may be reflective of newer US technology being more sensitive. Concordant with nearly all prior studies, calcifications and cystic changes were not seen in the cohort.…”
Section: Imaging Characteristicsmentioning
confidence: 81%
“…Plantar fibroma may be heterogeneous and hypoechoic (76%) or isoechoic (24%) relative to the plantar fascia [3, 28]. Posterior acoustic enhancement (20%), cystic components, and intratumoral hypervascularity (8%) have also been described [28, 29]. …”
Section: Plantar Fibromatosismentioning
confidence: 99%
“…Small intranodular cystic components causing posterior acoustic enhancement may also be present; Haun et al in 2011 reported a case of plantar fibroma that showed myxoid stromal degeneration and cysts histologically. (9) Sonoelastography is useful as a supplementary technique in musculoskeletal imaging. It provides qualitative information about the relative elasticities of soft tissues by measuring how they respond to applied stresses, using either shear-wave propagation or strain application (i.e.…”
Section: Discussionmentioning
confidence: 99%